2013
DOI: 10.1117/12.2002538
|View full text |Cite
|
Sign up to set email alerts
|

Nanoelectroablation for human carcinoma therapy

Abstract: We have developed a low energy direct current pulsed electric field therapy for tissue ablation. This therapy applies 100 ns long electric pulses 30 kV/cm in amplitude using a contact electrode and triggers apoptosis in the treated tissue. Here we review the progress that has been made in understanding the mechanisms and targets of nanosecond pulsed electric fields (nsPEF) when applied to cells and tissues. This work began in 2001 in the laboratory of Karl Schoenbach who collaborated with biologists Stephen Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Previous studies have demonstrated that a high electrical voltage intensity can induce cell apoptosis or death by causing electroporation of the cell membrane, thereby increasing the amount of intracellular Ca 2+ and reactive oxygen species that are toxic to cells. [48][49][50][51][52] In summary, upon adequate electrical stimulation (≈300 mV), the PGCNSH strengthens the effect of electrical signals because the interconnected conductive network formed by the PGC bio-nanosheets inside the PGCNSH provides short circuit for the electrical current to pass through neighboring electrodes, and thereby spatiotemporally imparting biochemical and biophysical cues to manipulate cell behavior. Consequently, the electrical stimulation and PGCNSH synergistically enhance the myoblast maturation.…”
Section: Pgcnsh As a Stable Electrical Stimulator Manipulating Cell Bmentioning
confidence: 99%
“…Previous studies have demonstrated that a high electrical voltage intensity can induce cell apoptosis or death by causing electroporation of the cell membrane, thereby increasing the amount of intracellular Ca 2+ and reactive oxygen species that are toxic to cells. [48][49][50][51][52] In summary, upon adequate electrical stimulation (≈300 mV), the PGCNSH strengthens the effect of electrical signals because the interconnected conductive network formed by the PGC bio-nanosheets inside the PGCNSH provides short circuit for the electrical current to pass through neighboring electrodes, and thereby spatiotemporally imparting biochemical and biophysical cues to manipulate cell behavior. Consequently, the electrical stimulation and PGCNSH synergistically enhance the myoblast maturation.…”
Section: Pgcnsh As a Stable Electrical Stimulator Manipulating Cell Bmentioning
confidence: 99%